2013
DOI: 10.2478/s11756-013-0192-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of different PCR-based marker systems for assessment of Iris pumila genetic diversity

Abstract: Abstract:We investigated informativeness and effectiveness of different marker types (ISSR, IRAP, REMAP, RGAP and LP-PCR that employ primers based on the conservative sequences of abiotic stress response genes) to study genetic diversity of Iris pumila L. By the number of amplicons per primer, number of polymorphic amplicons per primer and resolving power index (Rp), ISSR-markers were the most efficient followed by LP-PCR-markers. In order of decreasing value of indicators of genetic diversity "the percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…This observation is consistent with the increasingly popular trend where both neutral variation and adaptive variation are analyzed (Woodhead et al, 2005; Kirk & Freeland, 2011; Coscia et al, 2012; Bublyk et al, 2013). A reliable estimation of genetic variation plays a key role in conservation genetics because it supports evaluations of the present and future populations’ conditions (Kirk & Freeland, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This observation is consistent with the increasingly popular trend where both neutral variation and adaptive variation are analyzed (Woodhead et al, 2005; Kirk & Freeland, 2011; Coscia et al, 2012; Bublyk et al, 2013). A reliable estimation of genetic variation plays a key role in conservation genetics because it supports evaluations of the present and future populations’ conditions (Kirk & Freeland, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, in a Structure analysis performed by Singh et al (2013), the values of K were determined by the applied markers (K = 5 for SSRs, K = 15 for SNPs). Bublyk et al (2013), however, analyzed three types of markers amplifying non-coding sequences (RAPD, ISSR, inter-retrotransposon amplified polymorphism (IRAP)) and two types of markers based on conserved gene sequences: disease resistance (resistance gene analog polymorphism (RGAP)) and abiotic stress response (long primer polymerase chain reaction (LP-PCR)), and found different grouping patterns of Iris pumila individuals in PCoA diagrams for each marker. An analysis of I. pumila populations in the Structure program also produced ambiguous results (Bublyk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data determined the genetic diversity among several Iris species collected from different localities used RAPD (rapid amplified polymorphic DNA) and/or ISSR 41–47 . Different genetic markers [ISSR, inter‐retrotransposon amplified polymorphism (IRAP), retrotransposon‐microsatellite amplified polymorphism (REMAP), resistance gene analogue polymorphism (RGAP) and long primer (LP)‐PCR] were also used to study the genetic diversity of some Iris species, where the ISSR‐markers were found to be the most efficient 48 . Amplified fragment length polymorphisms (AFLPs) was used to determine diversity among I. pseudacorus population and other 14 Iris species 6,49 .…”
Section: Discussionmentioning
confidence: 99%
“…ISSR markers represent mostly noncoding regions of the genome flanked by SSRs. Several genetic studies of natural populations using ISSR markers have demonstrated their high variability, reproducibility [ 16 , 34 , 35 , 36 ] and relative ease of use in population-level studies in a variety of organisms [ 36 , 37 , 38 ] including plants [ 15 , 22 , 39 , 40 , 41 ]. ISSR markers are particularly useful for population genetic studies of rare species for which no previously characterized molecular markers are available [ 21 , 22 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%